PENERAPAN DAN PROSES PEMBUATAN KRIPIK PISANG DALAM MENINGKATKAN PENJUALAN DI DESA MANGLIAWAN KECAMATAN PAKIS KABUPATEN MALANG - Zainol Arifin; Ida Sugeng Suyani; Purwanto; Cakti Indra Gunawan; Dwi Asnawi Nurhananto (Universitas Merdeka Madiun, 2026)
Outreach regarding banana chip marketing strategies is crucial because marketing strategies aim to promote products using specific plans and tactics to increase sales targets while maximizing limited resources. This will lead to greater competitiveness and profitability in the future. Additionally, training and mentoring on the implementation of digital marketing technology are currently underway. Digital marketing is considered one of the most effective marketing techniques, leveraging digital media such as websites, social media, email marketing, and video marketing to help home-based banana chip businesses reach a wider market through the use of the Internet. The implementation of digital marketing has been proven to significantly increase in-store sales. Thus, the impact of this community service program effectively enhances community empowerment. By leveraging partners’ resources including skills, knowledge, accessibility, and income. The banana chip home industry can use these media to improve banana processing practices, producing high-quality banana chips and fostering economic sustainability in Mangliawan Village, Pakis Subdistrict, Malang Regency.